Combination of Acclimatization Media for The Primary Hardening Phase of Musa paradisiaca L. var. Kepok Tanjung Plantlets - Arianti, Tanti; Hasan, Rusdi; Setiawati, Tia; Nurzaman, Mohamad (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
Acclimatization is the last and critical stage in the in vitro culture of Musa paradisiaca L. var. kepok tanjung. The primary hardening phase of acclimatization is carried out so that plantlets can adapt from heterotrophic conditions to autotrophic conditions. This study aims to optimize the acclimatization media for M. paradisiaca L. var. kepok tanjung plantlets, an important factor in the acclimatization process. A completely randomized design was applied in this study using 13 different combinations of soil, cocopeat, and charcoal husk media. The observation parameters included morphological parameters (height, number of leaves, leaf area, pseudo-stem diameter, and survival rate) and physiological parameters (wet weight, dry weight, relative water content (RWC), and chlorophyll content index (CCI), which were analyzed using ANOVA or Kruskal-Wallis according to data assumptions. The results showed that all media combinations produced a 100% survival rate, with the best results shown by the cocopeat: charcoal husk (1:1) combination. This media combination provided the highest increase in height (1.05 ± 0.11 cm), pseudo-stem diameter (1.15 ± 0.12 mm), number of leaves (0.75 leaves), leaf area (121.06 ± 20 cm²), fresh weight (8.23 ± 2.99 g), dry weight (0.45 ± 0.16 g), CCI (23.2 ± 3.63), and the highest relative water content (98.47%). The combination of cocopeat and husk charcoal (1:1) was able to maintain moisture and provide good aeration for plantlet growth. Therefore, the combination of cocopeat and charcoal husk (1:1) is recommended as the most effective media for acclimatizing M. paradisiaca L. var. kepok tanjung plantlets in the primary hardening phase.